2018
DOI: 10.1088/1475-7516/2018/08/040
|View full text |Cite
|
Sign up to set email alerts
|

Exploring circular polarization in the CMB due to conventional sources of cosmic birefringence

Abstract: The circular polarization of the cosmic microwave background (CMB) is usually taken to be zero since it is not generated by Thomson scattering. Here we explore the actual level of circular polarization in the CMB generated by conventional cosmological sources of birefringence. We consider two classes of mechanisms for birefringence. One is alignment of the matter to produce an anisotropic susceptibility tensor: the hydrogen spins can be aligned either by density perturbations or CMB anisotropies themselves. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 62 publications
2
57
0
Order By: Relevance
“…That work builds upon a re-calculation [21], obtained with the TAM formalism [22,23], of circular polarization induced by photon-photon scattering, in Ref. [7], which itself extends several earlier analyses [2][3][4]6] of this effect. Note that the circular polarization induced through the photon-photon scattering is much larger than that induced through the photon-graviton scattering [20].…”
supporting
confidence: 54%
See 1 more Smart Citation
“…That work builds upon a re-calculation [21], obtained with the TAM formalism [22,23], of circular polarization induced by photon-photon scattering, in Ref. [7], which itself extends several earlier analyses [2][3][4]6] of this effect. Note that the circular polarization induced through the photon-photon scattering is much larger than that induced through the photon-graviton scattering [20].…”
supporting
confidence: 54%
“…This Thomson scattering does not, however, induce circular polarization. Recent work has shown that circular polarization can be generated, from primordial perturbations through post-recombination photon-photon scattering [2][3][4][5][6][7], at second order in the density-perturbation amplitude. Still, the mean value of the circular polarization, when averaged over the sky, is predicted to be zero.…”
mentioning
confidence: 99%
“…In the framework of cosmological perturbation theory, this arises as a second order effect, similar to the production of V due to photon-photon scattering [5,[7][8][9][10]14]. The relevant scattering process in this case is gravitonphoton scattering [32] .…”
Section: Primordial V-modes In the Cmbmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12]) has been on 'conventional' sources of circular polarization, e.g. Faraday conversion [3], which in many cases leads to a negligible large-scale CMB signal [5] ( 10 −14 K). However, no attempt has been made to quantify this expectation, and with this in mind, in this work we consider in detail the production and evolution of primordial circular polarization.…”
Section: Introductionmentioning
confidence: 99%
“…An additional possibility is that circular polarization can be generated at second order in cosmological perturbation theory, via photon-photon scattering. This was studied by [8], and expanded on in [9], which found a Faraday conversion (4.20)…”
Section: One-loop Qed (Second Order Cosmological Perturbation Theory)mentioning
confidence: 98%